PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV.A SD NEGERI 86 KOTA PEKANBARU - ', Nurbadra; ', Hamizi; ', Erlisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this reseach is to implement learning process and improve learning outcomes mathematic students with implementation of cooperative learning process type think pair share (TPS). In IV A grade student of elementary school 86 Pekabaru academic year 2014/2015 in competence Basic Standar use fraction in problem solving. Total subject this research is 22 students with 14 boys and 8 girls. With heterogen ability. This reaseach is class action reaseach divided into two cycles. Collective data this reaseach did observation and testSheet wiil analyze with descriptive narrative which purpose to describe about students and teacher activity during learning process happen. However result test will be analysis with minimal completeness criterian and analyzis mean score into know there is or not improvement result learning students before and after implementation of coopetive learning type think pair share (TPS) result of reseach show there is improvement result learning mathematic student IV A grade of elematary school 86 Pekanbaru . its show in teacher activity every meeting increased show from average of cycle I meeting I is 33,3, cycle II meeting II is 3,5. Cycle II meeting I is 3,67 and cycle II meeting II 3,83.However average of result learning students in basic score, daily test I and daily test II. Where average score is to, as and dauly test II average score is 95,45. From resul of reseach can be concluded is implementation of cooperative learing process type think pair share (TPS) can improve result learning IV A grade elemetary school 86 Pekan.baruKey words : Cooperative Learning Process Type Think Pait Share (TPS), Result Learning Mathematic